ANALISIS NARATIF PENGARUH PERSPEKTIF SUTRADARA PEREMPUAN DALAM PERFILMAN INDONESIA - Evelyn Talenta N. Tobing (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2021)
Film as a part of mass media certainly has a function in giving messages to the audience. Until now, the films circulating certainly contain the ideas and ideas of the creators. Ideas and ideas in filmmaking originated from the scriptwriter who produced the script. The role of the director is no less important in the next process, namely interpreting the script and producing it into a film. Among all the director's personal attributes that have an influence in making film works, gender is one of the backgrounds for different perspectives in expressing these ideas and ideas. In this case, gender can be interpreted as a social role attached to a particular gender. In this case, Indonesian cinema needs a new and different perspective by placing the perspective of women as what women want. This perspective will usually be brought by the director. How can directors create women's aesthetics, be it women's issues, politics, culture and other issues in films so that women directors can make film works as a medium to communicate and open up the widest possible perspective of women framed from women themselves in various ways to the audience.